The longitudinal relationship between employment and substance use among at-risk adolescents - Osilla, Karen Chan (J Child Adolesc Behav, 2015)
This paper explores the longitudinal association between employment and alcohol/other drug (AOD) use and consequences among an at-risk youth sample with a first-time AOD offense. This study extends previous research by examining the effects of more stable employment over time. Participants were adolescents referred to a diversion program (N=193) for a first-time AOD offense. Mean age was 16.6 (SD=1.1), 67% of the sample was male; and 45% Hispanic or Latino/a, 45% white; 10% other. We examined work intensity at program intake with AOD use, AOD-related consequences and risky social environment 180 days after the first survey. Greater work intensity was associated with greater peak drinks per occasion 180 days later and time spent around teens who use alcohol and marijuana; when controlling for age, gender, and race/ethnicity, work intensity was only associated with increased contact with teens who use marijuana. Work stability was not found to be associated with AOD-related use, outcomes, or reports of a risky social environment. Understanding how employment uniquely affects at-risk youth can help us determine policies and practices that may be needed to monitor the amount of time teens work.